2013
DOI: 10.1007/s12639-013-0395-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical coccidiosis in adult cattle

Abstract: Coccidiosis is caused by the protozoan parasite belongs to the genous Eimeria spp. which parasitizes the epithelium lining of the alimentary tract. Infection damages the lining of the gut causing diarrhoea and possibly dysentery. Coccidiosis is primarily a disease of young animals but can affect older animals that are in poor condition. In a farm, seven adult cattle had foul smell bloody diarrhoea, anorexia, emaciation condition, smudging of the perineum and tail with blood stained dung. Laboratory examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…3). This also indicates that the infestation with coccidia can still occur in adult cattle in accordance with previous reports (Sudhakara Reddy et al, 2015). Eimeria bovis and E. zuernii were reported here and they are noted as the most pathogenic species of Eimeria affecting cattle.…”
Section: Discussionsupporting
confidence: 93%
“…3). This also indicates that the infestation with coccidia can still occur in adult cattle in accordance with previous reports (Sudhakara Reddy et al, 2015). Eimeria bovis and E. zuernii were reported here and they are noted as the most pathogenic species of Eimeria affecting cattle.…”
Section: Discussionsupporting
confidence: 93%
“…Singla et al (2000) reported that toltrazuril @ 25 ppm for 2 days in drinking water was highly effective for the treatment of clinical outbreaks of hepatic coccidioisis in rabbits. Sulphadimidine was used to treat adult coccidiosis in cattle (Reddy et al 2013). Hygienic maintenance of rabbitry also plays an important role in control of the disease as the dampness of sheds favors the development of infective stages of coccidia which get transmitted by faecal oral route.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, Eimeria spp. are transmitted via the fecal-oral route and disease incidence is associated with several factors such as animal age; fecal contamination of feed, water, or soil; housing conditions (indoor or grazing); overcrowding; and poor hygiene [1,12,13]. Coccidiosis mainly causes problems in young animals, especially between 4 to 7 weeks after birth, and infected calves can spread the infection to other animals through feces containing infective oocysts in the environment and are also more susceptible to secondary bacterial and viral infections [13,14].…”
mentioning
confidence: 99%